2007
DOI: 10.1097/ftd.0b013e31802c573e
|View full text |Cite
|
Sign up to set email alerts
|

A Simple and Sensitive High-Performance Liquid Chromatographic Method for Quantification of PXD101, a Histone Deacetylase Inhibitor in Human Plasma

Abstract: PXD101, a new histone deacetylase inhibitor, is currently undergoing phase I/II clinical trials as an anticancer drug. This study describes a simple and sensitive high-performance liquid chromatography ultraviolet method developed for the quantification of PXD101 in human plasma samples to support such trials. Following solid phase extraction at room temperature, the analytes were separated on a 5 mum C18 150 x 2.1 mm column using gradient elution (mobile phase of acetonitrile and 25 mM NaH2PO4, pH 2.8) at a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Initially, we developed and validated a HPLC-UV assay with the lower limit of quantification (LLOQ) of 10 ng/mL for the determination of belinostat in human plasma [8]. However, concentrations in the plasma samples taken at 24 h after the start of infusion are usually too low to be quantified by the current HPLC-UV assay due to fast disposition of belinostat in the human body.…”
Section: Introductionmentioning
confidence: 99%
“…Initially, we developed and validated a HPLC-UV assay with the lower limit of quantification (LLOQ) of 10 ng/mL for the determination of belinostat in human plasma [8]. However, concentrations in the plasma samples taken at 24 h after the start of infusion are usually too low to be quantified by the current HPLC-UV assay due to fast disposition of belinostat in the human body.…”
Section: Introductionmentioning
confidence: 99%
“…The reviewed case studies of representative HDAC inhibitors in this report have adequately demonstrated the key bioanalytical challenges for the quantitation of various HDAC inhibitors. It is of interest to note that only a few HPLC methods ( n = 3) are reported for the quantification of various HDAC inhibitors (Mullangi et al ., ; Zhang et al ; Chassaing et al ., ) in biological samples. One of the methods used SPE and the other two methods used LLE.…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al . () quantified PXD101 (belinostat) in human plasma using SPE and separation was done using a reverse‐phase column connected to a UV detector. Mullangi et al .…”
Section: Discussionmentioning
confidence: 99%
“…A detailed survey of literature revealed that several HPLC and LC–MS/MS methods have been published for the determination of belinostat (BST), panobinostat (PST), rocilinostat (RST) and vorinostat (VST) individually [for BST – Kiesel et al (); Wang et al (); Zhang et al (); for PST – Estella‐Hermoso de Mendoza et al (); for RST – Gupta et al (); and for VST – Mullangi et al (); Liu et al (); Mohamed et al (); Wu, Chen, Wen, Zhang, and Lin (); Patel, Guichard, and Jodrell (); Parise, Holleran, Beumer, Ramalingam, and Egorin (); Du, Musson, and Wang ()] or along with other drug(s) [for VST with other drugs ‐ Yeo et al ()] in various biological matrices. We recently published an extensive review on bioanalytical methods for quantitation of HDACIs in various biological matrices using HPLC and LC–MS/MS (Suresh, Devaraj, Srinivas, & Mullangi, ).…”
Section: Introductionmentioning
confidence: 99%